Social system and strategic entry of women entrepreneur into informal economy in Lagos, Nigeria - Olutayo,; A. O.,; Yusuff, S.O. (Universiti Kebangsaan Malaysia, 2012)
Strategic entry of women into entrepreneurial activities and subsequent entrepreneurial development in informal economy within the social system has received little academic attention in spite of the fact that, entrepreneurship development is important to economic growth and decent work. It has also been found to promote quality of life. The focus of this paper is to examine the influence of social system in strategic entry of women into informal economic activities in Nigeria, using Yoruba women textile traders at Balogun market, Lagos State, South-West, Nigeria as a case study. The paper is anchored on Social action theory by Max Weber. The paper utilized only qualitative method of data collection. Eight focus group discussions, and forty In-depth – interviews were used to collect information from the women participants who were purposively chosen. The data reveal that parents, family members, and social friends had great influence in strategic entry of women into textile trading at Balogun market and subsequent development of women entrepreneurial activities. This information is essential towards policy formulation for women entrepreneurial development in informal economy.